Teaching creative thinking. A systematic look - Vásquez, Edith (Revista Innova Educación, 2021)
The objective was to systematize evidence of the development of creative thinking and its potentialities with a view from the educational field, highlighting the aspects of creativity in teachers. A systematic review of articles from the Proquest, Scopus, and Eric databases was carried out. Relevant information was selected. To obtain results, the information was systematized, considering the thematic axes as aspects of creativity, characteristics, and strategies for teaching creative thinking. It is concluded that creative teaching thinking is of great importance because it favors innovation. In addition, it is an essential aspect in today’s world, so it must be permanently strengthened and thus contribute to its development.